Factors affecting acid protease production by Mucor circinelloides MG603064.1 through SmF process: characterization and fromage frais making - Souhila Bensmail; Khaled Boudjema; Fethia Naimi-Fazouane; Samira Bensmail; Djamila Djouahra-Fahem; Fatiha Ferhoum; Nassima Bourfis (BioTechnologia, 2023)
The exploitation of food industry wastes and their conversion into value-added products present a promising and continuously growing field, given the diversity of elaborated wastes. The current work aimed to utilize sweet cheese whey as a growth medium for acid protease production by a local fungus strain. The biochemical and physicochemical properties of the cheese whey, such as pH, conductivity, chemical oxygen demand, biological oxygen demand (BOD 5 ), total nitrogen and protein contents, and mineral salts, were assessed using various analytical methods. The effect of certain parameters on acid protease production by Mucor circinelloides MG603064.1 through the SmF process was investigated using the conventional design method “One factor at a time”. Subsequent to characterization, the crude extract was used in a trial to create fromage frais , compared to the commercial rennin CHY-MAX ® Powder Extra. Cheese whey characterization revealed its richness in total nitrogen (1.044±0.044 g/l), protein content (6.52±0.04 g/l), and principal mineral salts: calcium (1.637±0.037 g/l), phosphorus (1.173±0.023 g/l), and chloride (1.66±0.09 g/l). The optimal values of the SmF process for acid protease production, such as the inoculum size, beef extract, and KH 2 PO 4 supplements, the initial pH of cheese whey, and incubation temperature were, respectively, 11% (v/v), 0.4% (w/v), 0.5% (w/v), 5.5, and 30̊C. Under these conditions, the lowest milk-clotting time of 290 s was achieved, representing an 18.41-fold increase com¬pared to the initial step using the unoptimized medium. The enzyme showed maximum milk-clotting activity at pH 5, a temperature of 60̊C, and in the presence of 0.025 M of CaCl 2 . The enzyme activity also significantly im¬proved with sonication (35 kHz) for 10 min. The crude extract of M. circinelloides ensured the production of fresh cheese samples with characteristics roughly similar to those obtained by the control (CHY-MAX ® rennin). The acid protease of M. circinelloides could successfully substitute the conventional rennin in the manufacture of fresh cheese.